IDDF2019-ABS-0153 Clinical significance of seprase and connexin-43 expression in gastric carcinoma. (7th June 2019) - Yin, Fangrui; Hua, Yunqi; Liu, Xianfeng; Yang, Yongyan; Wang, Chenlin; Li, Xi; Huang, Ying
Abstract : Background: To investigate the expression of connexin43( Cx43) and Seprase protein in gastric carcinoma and their clinical significance. Methods: Immunohistochemical method was used to detect the expression of Seprase and connexin 43 proteins in 45 specimens of gastric carcinoma and 15 specimens of paired adjacent normal gastric tissue. The relationship between their expression and the clinicopathologic characteristics were statistically analyzed. Results: 1: The positive rate of Seprase protein in gastric carcinoma was 71.11%(32/45) higher than that in normal tissue 20.00%(3/15) and with statistical significance (χ 2 =6.67, p=0.01); The positive rate of connexin 43 protein in gastric carcinoma was 68.89%(30/45) lower than that in normal tissue 100%(15/15) and with statistical significance(χ 2 =12.09, p=0.001). 2: Connexin 43 protein was related to the age and the degree of tissue differentiation of gastric carcinoma (P<0.05), Seprase protein was related to the age and the subtype of gastric carcinoma patients (P<0.05).3: Overall survival rates of patients with seprase and Connexin 43 expression were detected, Connexin 43 expression was an independent prognosis factor; meanwhile, seprase was correlated with the survival of the patients with gastric carcinoma in our study. Conclusions: In gastric carcinoma, Connexin 43 appeared down-expression and seprase appeared up-regulation, That may play important roles in the invasion and metastasis of gastric carcinoma, then provide a new direction for target therapy.